Menggali Kemampuan Anak Melaui Progresif Learning - Pebriani, Ela; Partikasari, Rika; Nurwita, Syisva; Ramadhani, Yani; Merdiana, Leni (Jurnal Dehasen Mengabdi, 2024)
Progressive learning is one of the schools of education that applies progressivism in the education system. This way of learning was born as a correction to the formal education system which was considered rigid and very traditional. This learning assumes that education must be based on the nature of humans as social creatures who learn best when they are in real life situations. The implementation of this PKM aims to educate PAUD teachers in the Alas Maras Seluma area to explore children's abilities through progressive learning.